2019
DOI: 10.1111/and.13277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sperm morphology and nuclear sperm quality in SPATA16‐ and DPY19L2‐ mutated globozoospermic patients

Abstract: The aim of this study was to compare the sperm morphology and nuclear sperm quality (sperm aneuploidy and DNA fragmentation) in two groups of globozoospermic patients: DPY19L2‐mutated patients (n = 6) and SPATA16‐mutated patients (n = 2). Results for these two groups were also compared to a group of fertile men (n = 25). Fluorescence in situ hybridisation was performed for chromosomes X, Y and 18. Sperm DNA fragmentation was evaluated by TUNEL assay. Sanger sequencing was performed for mutations screening of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…homozygous deletion is still concordant with the literature varying from 19% (Koscinski et al 2011) to 75% (Harbuz et al 2011) and very close to a recent study with 35% of DPY19L2 homozygous deletions among a large cohort of 63 patients (Alimohammadi et al 2020). In fact several globozoospermia studies recruited only total globozoospermic patients (Zhu et al 2013;Shang et al 2019;Ghédir et al 2019) and observed a much higher rate of DPY19L2-positive diagnosis. This is consistent with the correlation that we observed here between the high rate of globozoocephalic spermatozoa and the presence of loss of function DPY19L2 variants or deletions.…”
Section: Discussionsupporting
confidence: 91%
“…homozygous deletion is still concordant with the literature varying from 19% (Koscinski et al 2011) to 75% (Harbuz et al 2011) and very close to a recent study with 35% of DPY19L2 homozygous deletions among a large cohort of 63 patients (Alimohammadi et al 2020). In fact several globozoospermia studies recruited only total globozoospermic patients (Zhu et al 2013;Shang et al 2019;Ghédir et al 2019) and observed a much higher rate of DPY19L2-positive diagnosis. This is consistent with the correlation that we observed here between the high rate of globozoocephalic spermatozoa and the presence of loss of function DPY19L2 variants or deletions.…”
Section: Discussionsupporting
confidence: 91%
“…However, to date only a few globozoospermic patients have been examined. Most studies used the TUNEL assay to evaluate sperm DNA integrity and their results are generally in agreement with our findings, suggesting a high alteration of sperm DNA in globozoospermia [ 12 , 24 , 34 , 35 , 36 , 37 , 47 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Only a few studies claimed that globozoospermic men had similar chromatin and DNA integrity as fertile men [ 33 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since SPATA16 is highly conserved in mammals, these findings could explain why no alterations of this gene were found in the globozoospermic patients examined in our study. However, analysis of SPATA16 exon 2 revealed a new deletion in two unrelated Tunisian men, which could explain the globozoospermic phenotype [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 86 articles met our inclusion criteria and, therefore, were included in this systematic review ( Fig. 2 ) [ 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106…”
Section: Resultsmentioning
confidence: 99%
“…A total of 49 articles evaluated the prevalence and type of genetic abnormalities present in patients with globozoospermia [ 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 ] ( Table 3 ). The gene more frequently involved in the pathogenesis of globozoospermia is DPY19L2 and the mutation most frequently described is the deletion of the entire gene that, which has been reported to have a prevalence ranging from 22.2% [ 98 ] to 83.3% [ 105 ].…”
Section: Resultsmentioning
confidence: 99%